Optimizing Financial Performance and The Value of Energy Companies Through the Implementation of Enterprise Resource Planning - Devli Ananda Putra; Erwin Saraswati (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
This research evaluates the effect of Enterprise Resource Planning (ERP) implementation on the financial performance and firm value of energy sector companies listed on the Indonesia Stock Exchange. The research background highlights the importance of the ERP system's role in upgrading operational efficiency and company productivity, especially in the energy sector, which plays a vital role in national economic growth. This research examines the relationship between ERP and two dependent variables (return on investment and Tobin's Q), while controlling for company size, leverage, and company age. This research uses secondary data from the financial statements and annual reports of energy sector companies listed on the IDX between 2019 and 2022, and analyzes them using multiple linear regression. The findings indicate that ERP implementation has a significant positive effect on the ROI of energy sector companies, but does not affect the Tobin's Q ratio. These findings support the Resource-Based View theory, have implications for investors and company management, and help fill gaps in the existing literature.